Crafting a Tailored Digital Picture Storybook to Elevate the Pancasila Student Profile: Insights from Needs Analysis - Mynaryathy Mynaryathy; Wiwik Wijayanti (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to describe the needs analysis results for developing a digital picture storybook to enhance the Pancasila Student Profile of the 1st-grade elementary school students. This type of research is research and development (RD). The development model used is Borg and Gall. The population in the study were 1st-grade students and homeroom teachers of  elementary schools in Bantul Regency. The instruments were needs-analysis questionnaires, preliminary observation guidelines, preliminary interview guidelines, and literature. Data were analyzed by descriptive analysis. Based on the research results, it was concluded that students and teachers need digital picture storybooks to increase the Pancasila student profile of the students. The developing digital picture storybook is designed to fit the student's characteristics and the existing resources. It is an Android-based application that provides a story about the Pancasila Student Profile. It uses the Calibry font type with appropriate colors. The digital picture storybook can be operated without the internet. From the results of the needs analysis,  schools do not yet have digital storybook facilities. Teachers still rely on textbooks from the government and worksheets from publishers for teaching and learning activities. Digital picture storybook is relevant to the Merdeka Curriculum in the subject of Bahasa Indonesia in phase A (Class I) with reading and viewing elements.